ANALISIS RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN PT CAMPINA ICE CREAM INDUSTRY TBK PERIODE TAHUN 2020-2022 - Dita Retnaningtias; Candra Sigalingging (Mount Hope Management International Journal, 2024)
The aim is to assess financial achievements and performance based on the liquidity and profitability ratio aspects of PT Campina's financial reports for the 2020-2022 period. Research data is processed and analyzed using a descriptive quantitative approach to explain the picture of financial data in a more measurable manner. PT Campina's financial performance, in terms of liquidity ratios, is in the very good category and in liquid condition. Shown by an average current ratio of 12.42 times; very current ratio, namely 10.4 times; cash ratio of 8.31 times; cash turnover ratio, namely 1.43 times; and inventory to net working capital of 17.7%. This means that the company is optimal in paying its current debts on time or when they are billed. Meanwhile, in terms of profitability ratios, it is in the poor category because the ratio is far below industry standards. Indicated by an average net profit margin of 8.4%; ROI is 8%; ROE is 9.1%; and ROA of 8%. This condition means that the company has not optimally carried out its operations, especially to obtain profits from marketing its products.